2013
DOI: 10.2298/gensr1301087z
|View full text |Cite
|
Sign up to set email alerts
|

Soluble free phenolic compound contents and antioxidant capacity of bread and durum wheat genotypes

Abstract: The objective of this study was to determine phenolic compounds and the total antioxidant capacity in the grain of ten bread (T. aestivum L.) and ten durum (T. durum Desf.) wheat genotypes. Soluble free forms of total phenolics, flavonoids, PVPP (polyvinylpolypyrrolidone) bound phenolics, proanthocyanidins and phenolic acids were investigated. In addition, the correlation coefficients between total antioxidant capacities and the concentration of different soluble free phenolic compounds, as well as betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The authors cited detected them only in the red class of wheat grain, while phlobaphenes may be formed from chemically related proanthocyanidins (Young et al, 1985). Possible misclassification of both these groups of chemical compounds may be a reason for the lack of conformity concerning the content of proanthocyanidins in bread wheat (Stehno et al, 2011;Lukow et al, 2012;Žilić et al, 2013). The average endosperm hardness of the hybrid cultivars, as well as of the 'Bogatka', was on similar level -approx.…”
mentioning
confidence: 99%
“…The authors cited detected them only in the red class of wheat grain, while phlobaphenes may be formed from chemically related proanthocyanidins (Young et al, 1985). Possible misclassification of both these groups of chemical compounds may be a reason for the lack of conformity concerning the content of proanthocyanidins in bread wheat (Stehno et al, 2011;Lukow et al, 2012;Žilić et al, 2013). The average endosperm hardness of the hybrid cultivars, as well as of the 'Bogatka', was on similar level -approx.…”
mentioning
confidence: 99%
“…The resulting extract was used to determine the total phenol content. The phenol content was measured using Folin-Ciocalteu (Merck, India) reagent, following the method described by Zilic et al [15] with minor modifications. The total phenol content of each sample was expressed as milligrams of catechol equivalents (CE) per gram of brown rice flour.…”
Section: Analysis Of Amylose Protein and Total Phenol Contentmentioning
confidence: 99%
“…inhibition rate was obtained from Ç.1252 cultivar (3.76%), and the lowest value was obtained from Selçuklu-97 cultivar (3.06%) (Table 2). Zilic et al (2013) reported that the antioxidant capacity measured as DPPH . radical scavenging activity was similar in bread and durum whe Table 1.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…inhibition rate was obtained from Ç.1252 cultivar (3.76%), and the lowest value was obtained from Selçuklu-97 cultivar (3.06%) (Table 2). Zilic et al (2013) reported that the antioxidant capacity measured as DPPH . radical scavenging activity was similar in bread and durum wheats, but there were significant differences between genotypes within the species; it supports our study showing that statistically significant changes in DPPH .…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%